Motivation, Activities and Bariers to the Corporate Social Responsibility Implementation in the Czech SME Manufacturing Company - Munzarová, Simona; Vávra, Jan; Havlíčková, Markéta (STEF92 Technology Ltd., 2017)
Small and medium sized companies (SMEs) play a vital role in the securing and building a sustainable and responsible business environment of a particular region. SMEs approach to the surroundings may be based on completely different activities than large enterprises apply. The paper aims to evaluate the possibilities of implementation of social responsible activities in a selected Czech SME. In an effort to increase the continued low level of ethical character of the Czech business environment, it is SMEs that can also play an important role. The results in the paper are brought by analysis that was carried out by the means of a primary qualitative research, using the methods of in-depth interviews with owners and employees of one manufacturing SME company. The general methods applied were: analysis, comparison and synthesis. The paper identifies the main motivating factors for the implementation of CSR activities, analyses implemented socially responsible activities, possible sources of CSR innovations, adopted CSR tools, perceived benefits and barriers of CSR activities in the SME. Contribution of the article can be seen primarily in defining the characteristics of the SMEs approach to the socially responsible behavior, primarily due to the fact that the general assumptions of functioning, including the implementation of CSR into business practice, useful for large organizations at which the attention is mostly focused, have not been usually useful for SMEs.
Motivace, aktivity a bariéry implementace Společenské odpovědnosti v českém výrobním MSP podniku
Keywords: Corporate social responsibility; Small and medium sized company; Innovations; Benefits of CSR; Barriers of CSR; společenská odpovědnost organizací; malé a střední podniky; inovace; přínosy CSR; bariéry CSR